Rancang Bangun Mesin Pengering Ikan Memanfaatkan Sirkulasi Udara Panas Bagi Nelayan Desa Lekok Pasuruan - Mochammad Angga Syahputra; Vivin Wahyu Nabila; Juni Arif Muzaki; Dwi Songgo Panggayudi; Reynanda Bagus Widyo Astomo (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2021)
The Indonesian region, which has a tropical climate and has a wide sea, is one of the factors that make the population a fisherman. Fishermen from Pasuruan Regency, especially Lekok Village, are one of the producers of high quality marine products so that production reaches foreign exports. This study aims to develop the productivity of marine products in Lekok District, Pasuruan Regency which is constrained by the process of drying fish. Using research methods of literature and empirical studies, an automatic fish drying machine is designed by utilizing a hot air blower which is controlled by a thermistor and accompanied by a rotating system so that the results resemble manual drying using solar radiation. From the results of data analysis and system testing, it shows that the quality of fish that is dried with a rotary system is more effective than drying machines in general, such as the rack type because the results of drying fish are more even. The test results for the drying process require a temperature setting of 45-50 degrees within 220 minutes to reach a moisture content of 0.38% with a drying machine capacity of 32.5 kilograms.